Sub-acute Toxicity Assessment of Taxol Isolated From Fusarium Solani, an Endophytic Fungus of Taxus Brevifolia, in Wistar Rats and Analyzing Its Cytotoxicity and Apoptotic Potential in Lung Cancer Cells - Kuriakose, Gini C.; Arathi, B. P.; Divya Lakshmanan, Mangalath; Jiby, M. V.; Gudde, Ramachandra Subbaraya; Jayabhaskaran, C. (Frontiers in Oncology, 2020)
Limited availability of Taxol, from plant sources has prompted the scientific world to look for alternative, as chemical synthesis, tissue cultures of the Taxus species, to meet the increasing demand for the drug. However these alternative means are expensive or resulted in low yield. Previously we have reported that F. solani isolated from T. Celebica produced taxol and its precursor baccatin III in liquid grown cultures and it exhibited promising anti-cancerous effects in certain cancer cell lines. In the present study we examined sub-acute toxicity of fungal taxol (FS) in Wistar rats according to OECD guidelines. The sub-acute oral administration of FS up to 500 mg/kg for a period of 28 days appears to be safe in rats, and did not cause severe treatment-related toxicity or treatment related death. The observed changes in body weight, histopathology, haematological and biochemical parameters, and organ weight were not significant compared to control groups of animals. The results suggest that FS is relatively safe when administered orally in rats. The antiproliferative and apoptosis inducing activities were studied in A549 (human lung cancer) cell line. FS arrested the cells at S and G2/M phase leading to apoptosis. The characteristic molecular signatures of apoptosis such as externalised phosphatadyl serine, DNA fragmentation, and Nuclear and chromatin condensation were observed upon FS treatment. FS triggered the generation of ROS in A549 cells and elicited cell death by both extrinsic as well as mitochondria mediated intrinsic pathway of apoptosis. These results indicate that endophytic fungi isolated from medicinal plants may serve as potential sources of the anti-cancerous compounds with little side effects.